2023
DOI: 10.18174/583342
|View full text |Cite
|
Sign up to set email alerts
|

De invloed van bodemverdichting op dewater- en luchthuishouding in de bodem en op de plantontwikkeling : literatuuronderzoek

Abstract: Dit onderzoek is uitgevoerd door Wageningen Environmental Research in het kader van het onderzoeksprogramma Bodemverdichting Verdiept (BoVer).BoVer is een driejarig onderzoeksprogramma gesubsidieerd door de TKI Deltatechnologie.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 115 publications
0
4
0
2
Order By: Relevance
“…There is a mechanical impedance caused by lack of space to store displaced soil particles by root growing. A compacted soil also has a negative effect on water infiltration, water retention, gas permeability and exchange, nutrient cycle and habitat for soil organisms, resulting in suppression of root growth (Bakema et al, 2023). Lipiec et al (2012) found, in an experiment with undisturbed soil samples, a reduction of 50% of the root length for barley and 79% for triticale in compacted soil compared to non-compacted soil.…”
Section: Biomechanical Recovery (Biosubsoiling)mentioning
confidence: 99%
See 3 more Smart Citations
“…There is a mechanical impedance caused by lack of space to store displaced soil particles by root growing. A compacted soil also has a negative effect on water infiltration, water retention, gas permeability and exchange, nutrient cycle and habitat for soil organisms, resulting in suppression of root growth (Bakema et al, 2023). Lipiec et al (2012) found, in an experiment with undisturbed soil samples, a reduction of 50% of the root length for barley and 79% for triticale in compacted soil compared to non-compacted soil.…”
Section: Biomechanical Recovery (Biosubsoiling)mentioning
confidence: 99%
“…Another physical quantity to express the effect of soil compaction on root growth is dry bulk density. A dry bulk density of ~1.47-1.58 g cm -3 in clay soils and 1.85 g cm -3 in sandy soils is obstructing root growth (Bakema et al, 2023). (Bakema et al, 2023).…”
Section: Biomechanical Recovery (Biosubsoiling)mentioning
confidence: 99%
See 2 more Smart Citations
“…Beperkte wortelgroei in een verdichte bodem heeft ook een negatief effect op de infiltratie en retentie van water en de doorlatendheid voor gassen en gasuitwisseling. Dit onderdrukt de nutriëntencyclus en heeft een negatieve invloed op de habitat voor bodemorganismen (Bakema et al, 2023). Zo werd in een experiment in verdichte grond gevonden dat de wortellengte voor gerst (Hordeum vulgare) 50% minder was vergeleken met niet-verdichte grond, en 21% minder voor triticale (Triticosecale) (Lipiec et al, 2012).…”
Section: Het Procesunclassified